Molecular genetics is on the guard of the law - L. I. Kucherenko; I. V. Pavliuk; O. V. Khromylova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Molecular genetics is one of the key tools of modern medicine. With its help, scientists can study the structure and function of DNA, decode genetic codes, and develop new treatments. In the conditions of the modern world, where global crises, such as the war in Ukraine, occur more and more often, the role of molecular genetics goes far beyond standard medical tasks and becomes critically important for solving social, legal and humanitarian problems. Thus, molecular technologies have become an important tool both in the public health maintenance and in the human rights protection.